Interactive Media Development Using Augmented Reality Applications to Improve Student Learning Outcomes in Mathematics Learning in Grade V Elementary School - Zora Oktama; Weni Yulastri; Annisa Kharisma (Journal of Educational Sciences, 2026)
This study aims to develop and test the feasibility of interactive media based on Augmented Reality (AR) in Mathematics learning on spatial geometry material in fifth grade elementary schools. The development of this media uses a 4D development model consisting of four stages, namely Define, Design, Develop, and Disseminate. In the Define stage, a needs analysis is conducted through observation and interviews with teachers to identify obstacles in Mathematics learning. The Design stage includes designing the AR media display and compiling spatial geometry materials according to student characteristics. The Develop stage includes the creation and validation of the media by material experts, language experts, and media experts, which resulted in validation scores of 96.42%, 93.75%, and 95.83%, respectively, with a very valid category. The Disseminate stage was conducted through trials at SDN 10 Koto Tinggi Surian and SDN 08 Tambang Surian to measure the practicality and effectiveness of the media. The results of the practicality test showed a student response of 91.67% and a teacher response of 94.15%, with a very practical category. Meanwhile, the results of the effectiveness test using the N-Gain Score analysis showed a significant improvement in student learning outcomes, with an average score of 0.74 at SDN 10 Koto Tinggi Surian and 0.71 at SDN 08 Tambang Surian, which are in the high category. Thus, the AR-based interactive media developed using the 4D model has proven valid, practical, and effective in improving understanding of spatial concepts and supporting the implementation of the Independent Curriculum.